A Study on the Historical Foundations of Jewish Orientalism: Ignaz Goldziher Example - Hafize Yazıcı (Hadith, 2020)
While Christians had a long history of Islamic Studies in the West, Jewish also made remarkable contributions to this field beginning from the early periods, and they have had a pioneering role in this field thanks to the scientists they educated. Although Jewish Orientalism differs from Christian Orientalism as for its fields of interest and subjects, it depends on European scientific methods in terms of the methods it uses. In contrast to Christian Orientalism, Jewish Orientalism placed Judaism at the center and aimed to respond to the criticisms of Christians against Judaism. From this aspect, they both wanted to defend Judaism against Christianity, and to reform Judaism. There are many political, religious and intellectual reasons for Jewish Orientalism to turn towards Islām Studies. Jewish Orientalism can be classified in three parts in the historical process, these are formation period, maturation period and post-Zionism period. While Abraham Geiger (1810-1874) and Gustav Weil (1808-1889) were among the founding fathers of Jewish Orientalism, the maturation period for Jewish Orientalism came true thanks to Ignaz Goldziher (1850-1921) and the ideas he suggested had a constituent characteristic of forming the paradigm about Islām and its traditions in the West. In this study, the emergence of Jewish Orientalism, its periods and the reasons of studying Islām will be investigated and, the life of Ignaz Goldziher, and his thoughts on Islām in general and ḥadīt̲h̲ in particular will be examined, and the role of Goldziher in Jewish Orientalism will be tried to be revealed.